2015
DOI: 10.1007/bf03356556
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Studies Between Field Isolates of Magnaporthe oryzae Resistant and Sensitive to Scytalone Dehydratase Inhibitors of Melanin Biosynthesis (Mbi-Ds) and Decline of Frequency of Resistant Isolates at a Rice Field

Abstract: Fitness of isolates of Magnaporthe oryzae resistant to scytalone dehydratase inhibitors of melanin biosynthesis (MBI-Ds) was studied in comparison with sensitive isolates. We found no significant differences in pathogenicity between sensitive and resistant isolates. In competition studies, sensitive isolates became dominant after four to six successive inoculations from the diseased rice seedlings infected by both sensitive and resistant isolates, irrespective of the initial ratio of these isolates. No reverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Suzuki et al (2010) monitored the emergence frequency of resistant isolates from fields in Kyushu after MBI-D applications were stopped and showed that the frequency declined. 6) Kimura and Fujimoto (2015) reported that the emergence frequency of resistant isolates decreased rapidly without the presence of MBI-Ds in laboratory and field tests. 7) Kimura and Fujimoto (2017) also reported that the resistant SH activity was lower than the sensitive SH activity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Suzuki et al (2010) monitored the emergence frequency of resistant isolates from fields in Kyushu after MBI-D applications were stopped and showed that the frequency declined. 6) Kimura and Fujimoto (2015) reported that the emergence frequency of resistant isolates decreased rapidly without the presence of MBI-Ds in laboratory and field tests. 7) Kimura and Fujimoto (2017) also reported that the resistant SH activity was lower than the sensitive SH activity.…”
mentioning
confidence: 99%
“…6) Kimura and Fujimoto (2015) reported that the emergence frequency of resistant isolates decreased rapidly without the presence of MBI-Ds in laboratory and field tests. 7) Kimura and Fujimoto (2017) also reported that the resistant SH activity was lower than the sensitive SH activity. 8) Previous reports suggested that P. oryzae isolates resistant to MBI-Ds paid a fitness penalty to acquire the resistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7) These previous reports suggested that MBI-D-resistant isolates paid a fitness penalty for acquiring their resistance and that sensitive isolates would be dominant without MBI-D pressure. However, the re-use of MBI-Ds has not been implemented in the area where resistant isolates were widely found.…”
mentioning
confidence: 98%